Tourism-Induced Deforestation in Batu City: Implications for Sustainable Development - Ayu Fitriatul Ulya; Fitria Earlike Anwar Sani; Andini Risfandini; Daria Alviota Hamat (Goodwood Publishing, 2026)
Purpose: This study examined the spatial pattern of tourism-related deforestation and vegetation recovery in Batu City to support sustainable tourism management. Research Methodology: This study applies a Geographic Information System (GIS)-based spatial analysis using secondary data from Global Administrative Areas (GDAM), Google Points of Interest (POI), and Global Forest Watch. Thematic layers, including land capability, slope, land use, and tourism distribution, were analyzed using overlay and buffer techniques in Geographic Information System for ArcGIS and Quantum Geographic Information System (QGIS). Data validation and standardization were performed to minimize bias and ensure reliability. Results: The findings highlight that unregulated infrastructure development for tourism accelerates deforestation and threatens the ecosystem balance. Comparative analysis with previous studies supports the conclusion that unsustainable tourism practices contribute to biodiversity decline Conclusions: Tourism expansion in Batu City has driven deforestation and uneven vegetation change, and current restoration efforts remain insufficient. Sustainable spatial planning, stronger reforestation, and ecotourism promotion are required to balance tourism growth and environmental conservation. Limitations: This study relied on secondary remote sensing data and did not incorporate field-based ecological verification or socio-economic data on tourism operators and communities. The analysis also does not distinguish between deforestation drivers beyond tourism-related land conversion. Contributions: This research provides localized spatial evidence of tourism-driven deforestation in Batu City, addressing the gap in empirical studies on the ecological footprint of tourism in Indonesia. The findings offer practical guidance for policymakers to integrate forest conservation into sustainable tourism planning.